PENERAPAN KEPATUHAN MINUM OBAT DAN AKTIVITAS TERJADWAL MEMBACA AL-QUR’AN TERHADAP PENURUNAN TANDA DAN GEJALA PASIEN HALUSINASI - Margaretha, Meysa; Riyana, Asep; Kustiawan, Ridwan (Fakultas Ilmu Kesehatan Universitas Siliwangi, 2025)
Hallucinations are disturbances in sensory perception of an external stimulus object, this sensory disturbance penetrates all five senses. Hallucinations are one of the symptoms of mental disorders, patients experience changes in their sensory perception and experience false sensations of hearing, seeing, tasting, touching or smelling, feeling stimuli that are not actually psychiatric patients experiencing a change in reality orientation. The aim is to determine the characteristics of the patient before carrying out the scheduled activity of reading the Qur'an, implementing the scheduled activity of reading the Qur'an in schizophrenic patients with hallucinations, implementing the implementation stage of the description of the implementation of observing the implementation of Nursing Care with the Implementation of Medication Compliance and Scheduled Activities: Reading Al-Qur'an Against Decreasing Signs and Symptoms of Hallucinations with a percentage of 82 percennt. This scientific paper uses case studies on 2 patients who experience hallucinatory sensory perception disorders. The results of this case study showed that both patients experienced a decrease in signs and symptoms of hallucinations. The conclusion of this case study is that the strategy of medication adherence and activity therapy: reading the Qur'an is effective in reducing hallucinations. Suggestions for families to be able to participate in providing nursing care to patients with hallucinatory sensory perception disorders so that patients feel there is support that can accelerate the healing process of their illness.